2019
DOI: 10.1148/radiol.2018181445
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Hyperthermia for Targeted Drug Release from Thermosensitive Liposomes: Results from a Phase I Trial

Abstract: To demonstrate the feasibility and safety of using focused ultrasound planning models to determine the treatment parameters needed to deliver volumetric mild hyperthermia for targeted drug delivery without real-time thermometry. Materials and Methods: This study was part of the Targeted Doxorubicin, or TARDOX, phase I prospective trial of focused ultrasound-mediated, hyperthermia-triggered drug delivery to solid liver tumors (ClinicalTrials.gov identifier NCT02181075). Ten participants (age range, 49-68 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…In addition, hyperthermia improves blood flow and permeability near tumor vessels, increasing nanoparticle extravasation [14,17]. Several thermo-sensitive liposomes have been formulated to attain maximum drug release in response to hyperthermia treatment [18][19][20][21][22][23][24][25][26][27][28][29]. One thermo-sensitive liposome currently in phase III clinical trials is ThermoDox.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hyperthermia improves blood flow and permeability near tumor vessels, increasing nanoparticle extravasation [14,17]. Several thermo-sensitive liposomes have been formulated to attain maximum drug release in response to hyperthermia treatment [18][19][20][21][22][23][24][25][26][27][28][29]. One thermo-sensitive liposome currently in phase III clinical trials is ThermoDox.…”
Section: Introductionmentioning
confidence: 99%
“…182,183 In a recent study, the trial demonstrated that the ThermoDox ® , designed to release targeted levels of doxorubicin into and around tumors with heat and ultrasound activation, increased doxorubicin delivery to tumors in the majority of liver cancer patients in a 10-patient trial. 184 In addition, photodynamic therapy (PDT) is a novel noninvasive medical application that utilizes a photosensitizing agent (PS) to kill pathological cells. The PS is a chromophore normally derived from porphyrins which absorbs light and then produces reactive oxygen species (ROS) that kill targeted cells.…”
Section: External Stimulimentioning
confidence: 99%
“…In another study, Gray et al [62] conducted a phase I trial study involving focused US-mediated hyperthermiatriggered drug delivery to solid liver tumors. The ten participants were treated from March 2015 to March 2017 using a clinically approved focused US system to release DOX from thermo-sensitive liposomes.…”
Section: Controlled Release Of Drugs From Micelles Andmentioning
confidence: 99%